Surgical management of a strangulated inguinal hernia in a Cynomolgus Monkey (Macaca fascicularis): a case report with discussion of diagnosis, and review of literature - Baptiste Sadoughi; Manon Dirheimer; Pierrick Regnard; Fanélie Wanert (Revue de Primatologie)
We report the emergency management of a strangulated indirect inguinal hernia in a male cynomolgus macaque. Severe shock was associated with swelling of the right inguinal and scrotal regions. Emergency surgery was performed with reduction of the hernia, unilateral castration and hermetic closure of the inguinal ring using mattress sutures. Enterectomy was not performed based on clinical evaluation of bowel’s integrity. The animal recovered well from the surgery and follow-up necropsy revealed perfect closure of the hernia without formation of adhesions at the surgical site. Strangulation and necrosis of intestinal loops in strangulated hernia are life-threatening conditions with a negative impact on both per-operative management and post-operative recovery. Early signs and symptoms suggestive of strangulated inguinal hernia and therapeutic options are discussed.